Cyber Counseling in Responding to Educational Challenges in the Society 5.0 Era: A Literature Review Study - Kurniati, Nadiya; Sari, Lyana Alvionita (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2025)
The Society 5.0 era sparks industrial activities that integrate advanced automation technologies with cyber technologies. It will affect every aspect of human life, especially in industry, health transportation, agriculture, and education. Education in the realm of guidance and counseling needs to innovate in adapting to the demands of the society 5.0 era. One form of innovation is the existence of cyber counseling services. A literature review study was used as a method in this study. The data collection process by examining various relevant reference sources related to cyber counseling from 28 articles published over the last 10 years. This study aims to examine the evolution of cyber counseling, as well as the innovation of guidance and counseling services required to address the challenges in education during the Society 5.0 era. The results show that in the implementation of cyber counseling services, there were several advantages and disadvantages that can be used as evaluation material in the development of cyber counseling service programs so that guidance and counseling are maintained in their existence in responding to educational challenges in the Society 5.0 Era.